STORYTELLING MELALUI DARING TERHADAP KEMAMPUAN KOGNITIF ANAK USIA DINI DI KELOMPOK BERMAIN (KB) NANDA CERIA BOCEK KARANGPLOSO KABUPATEN MALANG - Salimatul Ummah; Rosichin Mansur; Eko Setiawan (Jurnal Dewantara, 2021)
This study aimes to describe the implementation of online storytelling to early childhood cognitive abilities in KB Nanda Ceria, Bocek Karangpoloso Malang. this research uses a qualitative approach with a type of case study. The research subject were early childhood children aged 3-4 years, classroom teachers, and parents. Primary data of this study were obtained through in-depth interviews with research subject followed by obsernation and documentation as a process analysis. Furthemore, the data is reduced by classifying the result obtained. Each analysis was narrated descriptively and then concluded according to the focus of the study. Based on the result of the study, cognitive abilities of early chilhood in KB Nanda Ceria Bocek Karangploso Malang develop according to their age, but still not maximally stimulated. The implementation of online storytelling to early childhood cognitive abilities is carried out in several stages, starting from compiling learning activities, sharing learning activities to parents, antill people continuing storytelling with childrens at home. The inhibiting factors for the implementation of online storytelling to early childhood cognitive abilities lies in the ability of human resourses (HR), time, and children’s tendencies, while the supporting factors are quota assistance from the goverment and so many story references that theacers can get as storytelling material online.